THE INFLUENCES OF GENDER ROLE ON CHARACTERISTICS OF SUCCESSFUL MANAGERS - Oanh, p. (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2017)
The perceptions of successful managers as masculine people have been mentioned in previous studies that have created barriers for women on the path to conquer managerial positions. This study was to examine the relationships between gender stereotypes and the characteristics of the successful managers that were perceived by both gender students in the diversified cultural context of Asian Institute of Technology (AIT). The participants included 240 students from 20 countries studying in three main departments in AIT. The original Schein Descriptive Index with 92 items was used in this study with three different categories namely successful managers, men and women along with the calculation of intraclass correlation coefficients (ICC) was used to determine the degree of resemblance of successful managersmen, successful managers-women. The findings firstly indicated that “Think manager, think male” still existed at AIT, and further revealed that female participants viewed both women and men were quite similar to successful managers while male participants perceived women were different from successful managers. From then, some further feasible suggestions were pointed to eliminate gender stereotype in management and create the environment where males and females have equal chances to reach managerial positions.